Compositions for making ophthalmic lenses containing encapsulated light absorbing additives

CN117003928BActive Publication Date: 2026-10-30ESSILOR INTERNATIONAL(COMPAGNIE GENERALE D OPTIQUE)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311014970.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-08-09
Filing Date
2017-08-09
Publication Date
2026-10-30
Estimated Expiration
2037-08-09

AI Technical Summary

Technical Problem

然而,高量的包含在纳米颗粒和化妆品组合物中的UV吸收剂与用于制备眼科镜片的液体可聚合组合物不相容

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004391596860000161
    Figure BDA0004391596860000161
  • Figure BDA0004391596860000171
    Figure BDA0004391596860000171
  • Figure BDA0004391596860000191
    Figure BDA0004391596860000191
Patent Text Reader

Abstract

The present invention relates to a thermosetting composition for the manufacture of ophthalmic lenses that effectively absorb light without degradation of the light absorbing additive, said composition comprising an allylic monomer or oligomer, a catalyst, at least one light absorbing additive contained in nanoparticles, said nanoparticles being dispersed in the allylic monomer or allylic oligomer. The present invention also relates to the use of said composition and to the ophthalmic lenses obtained from said composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of patent application No. 201780047036.7, filed on August 9, 2017, entitled "Composition for Manufacturing Ophthalmic Lenses Containing Encapsulated Light Absorbing Additives". Technical Field

[0002] This invention relates to a thermosetting composition for manufacturing ophthalmic lenses that effectively absorb light, the composition comprising an allyl monomer or oligomer, a catalyst, and at least one light-absorbing additive contained in nanoparticles dispersed in the allyl monomer or allyl oligomer, without degradation of the light-absorbing additive during thermosetting. The invention also relates to the use of the composition and ophthalmic lenses obtained from the composition. Background Technology

[0003] Light that reaches and enters the human eye is divided into visible light (including wavelengths from about 380 nm to 780 nm) and invisible light, which includes light in the ultraviolet range (UV-A and UV-B light from about 280 nm to 380 nm) and light in the infrared range (near IR light from about 780 nm to 1400 nm).

[0004] UV light is known to be harmful to the human eye. In particular, it can accelerate eye aging, which can lead to early cataracts or more extreme conditions such as photokeratitis or snow blindness.

[0005] Blue light, also known as high-energy visible (HEV) light, corresponds to visible light in the blue-violet band between 380 nm and 500 nm. Prolonged exposure to blue light emitted from digital devices such as televisions, laptops, tablets, and smartphones, as well as fluorescent and LED lighting, is harmful because it can reach the retina. Certain ranges of blue light have been shown to cause photoretinitis; digital eye strain or computer vision syndrome, which includes blurred vision, difficulty focusing, dry and irritated eyes, headaches, neck and back pain; disruption of circadian rhythms; reduced melanin production; age-related macular degeneration; glaucoma; retinal degenerative diseases; breast and prostate cancer; diabetes; heart disease; obesity; and depression. Blue light in the range of approximately 420 nm to 450 nm is considered particularly harmful.

[0006] Damage from UV and blue light can be prevented by incorporating light-absorbing additives into ophthalmic lenses.

[0007] Three different methods can be used to manufacture light-absorbing ophthalmic lenses. The first method, as disclosed in European Patent No. 1085 349, involves immersing the polymer lens in a bath containing light-absorbing additives. However, this method increases the number of steps in the lens manufacturing process, which is not desirable in terms of cost and time.

[0008] The second method, as disclosed in U.S. Patent No. 5,949,518, involves coating the surface of an ophthalmic lens with a light-absorbing substance. However, incorporating high amounts of light-absorbing additives into the coating weakens its mechanical properties.

[0009] The third method, as taught in European Patent No. 1085 348, involves incorporating a light-absorbing additive into the bulk liquid formulation (i.e., prior to polymerization). In this document, a thermosetting composition comprising diethylene glycol dielyl carbonate or bis(β-cyclothiopropyl)sulfide monomer, diisopropyl peroxide dicarbonate (as a catalyst), and 2-(2-hydroxy-4-octyloxyphenyl)-benzotriazole (as a light-absorbing additive) is cast into a mold for a lens and heated until polymerization occurs. However, lenses obtained by this method are prone to undesirable yellowing due to the degradation of the light-absorbing additive.

[0010] The yellowing of lenses is caused by the interaction between free radicals and light-absorbing additives during polymerization. This yellowing effect is particularly pronounced when high concentrations of catalyst are used to initiate polymerization, especially with weakly reactive monomers such as allyl monomers.

[0011] For aesthetic reasons, and because yellowing of lenses can affect the wearer's color perception and ultimately reduce the lens's transmittance, lens yellowing is undesirable.

[0012] In particular, for lenses that absorb blue light, two yellowing effects may be superimposed. As mentioned above, the interaction between free radicals and light-absorbing additives causes yellowing. For light passing through the lens, some blue light is absorbed, resulting in the transmitted light appearing pale yellow to the lens wearer.

[0013] If less catalyst is used, yellowing of the lens may be prevented, but polymerization will not be complete and the mechanical properties of the lens will be unacceptable.

[0014] Patent application US20120188503 discloses the use of a milder catalyst, different from dicarbonate peroxide, to ensure that the absorption properties of azirporphyrin dyes withstand the polymerization process. Among the proposed alternative peroxides, peroxide esters and perketals are particularly preferred.

[0015] Patents such as EP 2282713, EP 2263788, and JP 3347140 describe UV absorbers encapsulated in mineral matrices for use in cosmetic applications to provide protection against sunspots. However, high amounts of UV absorbers contained in nanoparticles and cosmetic compositions are incompatible with liquid polymerizable compositions used in the preparation of ophthalmic lenses.

[0016] Therefore, there is a need for a thermosetting composition containing light-absorbing additives for manufacturing ophthalmic lenses, the ophthalmic lenses having a predetermined absorption spectrum that is unaffected during polymerization.

[0017] The applicant has discovered that this need can be met by encapsulating light-absorbing additives in nanoparticles dispersed in the thermosetting composition. Summary of the Invention

[0018] The first object of the present invention is a polymerizable liquid composition for manufacturing ophthalmic lenses, said composition comprising:

[0019] a) At least one allyl monomer or allyl oligomer

[0020] b) At least one catalyst for initiating the polymerization of the allyl monomer or allyl oligomer.

[0021] c) At least one light-absorbing additive contained in nanoparticles, said nanoparticles being dispersed in the allyl monomer or allyl oligomer.

[0022] A second object of the present invention is a method for preparing a polymerizable liquid composition according to the present invention, the method comprising the following steps:

[0023] a) Provide allyl monomers or allyl oligomers;

[0024] b) Provide a light-absorbing additive contained in nanoparticles, the nanoparticles being in the form of a powder of nanoparticles that can be dispersed in the allyl monomer or allyl oligomer, or in the form of a dispersion of the nanoparticles in a liquid that can be dispersed in the allyl monomer or allyl oligomer.

[0025] c) Provide a catalyst for initiating the polymerization of the allyl monomer or allyl oligomer;

[0026] d) Mix the allyl monomer or allyl oligomer, the light-absorbing additive contained in the nanoparticles, and the catalyst.

[0027] Another object of the present invention is the use of light-absorbing additives contained in nanoparticles for preventing degradation by catalysts that initiate the polymerization of allyl monomers or allyl oligomers, particularly for preventing yellowing of cured allyl-based ophthalmic lenses, wherein the nanoparticles are dispersed in a polymerizable liquid composition according to the present invention.

[0028] Another object of the present invention is an ophthalmic lens obtained by curing a polymerizable liquid composition according to the present invention.

[0029] Another object of the present invention is an ophthalmic lens, said ophthalmic lens comprising:

[0030] a) Optical substrate;

[0031] b) A coating obtained by curing a polymerizable liquid composition according to the invention onto the optical substrate.

[0032] The ultimate objective of this invention is an ophthalmic lens comprising a composite substrate, said composite substrate comprising:

[0033] a) A matrix obtained by polymerizing at least one allyl monomer or oligomer in the presence of a catalyst for initiating the polymerization of the allyl monomer or allyl oligomer.

[0034] b) Nanoparticles containing at least one light-absorbing additive, said nanoparticles being dispersed in the matrix. Detailed Implementation

[0035] polymerizable compositions

[0036] The polymerizable liquid composition according to the present invention comprises an allyl monomer or oligomer, a catalyst, and nanoparticles containing light-absorbing additives.

[0037] More specifically, the polymerizable liquid composition comprises:

[0038] a) At least one allyl monomer or allyl oligomer

[0039] b) At least one catalyst for initiating the polymerization of the allyl monomer or allyl oligomer.

[0040] c) At least one light-absorbing additive contained in nanoparticles, said nanoparticles being dispersed in the allyl monomer or allyl oligomer.

[0041] The allyl monomer or allyl oligomer contained in the composition according to the invention is a compound containing an allyl group. The compound may be selected from the group consisting of: diethylene glycol bis(allyl carbonate), ethylene glycol bis(allyl carbonate), oligomers of diethylene glycol bis(allyl carbonate), oligomers of ethylene glycol bis(allyl carbonate), bisphenol A bis(allyl carbonate), diallyl phthalates (such as diallyl phthalate, diallyl isophthalate, and diallyl terephthalate), and mixtures thereof.

[0042] The amount of the allyl monomer or oligomer in the polymerizable composition according to the invention may be from 20% to 99% by weight, particularly from 50% to 99% by weight, more particularly from 80% to 98% by weight, and even more particularly from 90% to 97% by weight, based on the total weight of the composition.

[0043] Specifically, the polymerizable composition may comprise, based on the total weight of the composition, from 20% to 99% by weight, particularly from 50% to 99% by weight, more particularly from 80% to 98% by weight, and even more particularly from 90% to 97% by weight, oligomers of diethylene glycol bis(allyl carbonate), or mixtures thereof.

[0044] The polymerizable composition may further comprise a second monomer or oligomer capable of polymerizing with the allyl monomers or oligomers described above. Examples of suitable second monomers include: aromatic vinyl compounds such as styrene, [α]-methylstyrene, vinyltoluene, chlorostyrene, chloromethylstyrene, and divinylbenzene; mono(meth)acrylates such as methyl methacrylate, n-butyl methacrylate, n-hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, methoxydiethylene glycol (meth)acrylate, methoxy polyethylene glycol (meth)acrylate, 3-chloro-2-hydroxypropyl methacrylate, stearate methacrylate, lauryl methacrylate, phenyl methacrylate, glycidyl methacrylate, benzyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 3-hydroxypropyl methacrylate, 3-phenoxy-2-hydroxypropyl methacrylate, and 4-hydroxybutyl methacrylate; Di(meth)acrylates, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 2-hydroxy-1,3-di(meth)acryloyloxypropane, 2,2-bis[4-((meth)acryloyloxyethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloyloxydiethoxy)phenyl]propane, and 2,2-bis[4-((meth)acryloyloxypolyethoxy)phenyl]propane; tri(meth)acrylates, such as trimethylolpropane tri(meth)acrylate and tetramethylolmethane tri(meth)acrylate; tetra(meth)acrylates, such as tetramethylolmethane tetra(meth)acrylate. These monomers can be used alone or in combination of two or more. In the above description, "(meth)acrylate" means "methacrylate" or "acrylate", and "(meth)acryloyloxy" means "methacryloyloxy" or "acryloyloxy".

[0045] The amount of the second monomer or oligomer in the polymerizable composition according to the invention may be from 1% to 80% by weight, particularly from 1% to 50% by weight, more particularly from 2% to 20% by weight, and even more particularly from 3% to 10% by weight, based on the total weight of the composition.

[0046] The catalyst included in the composition according to the invention is a catalyst suitable for initiating the polymerization of allyl monomers, such as organic peroxides, organic azo compounds, and mixtures thereof.

[0047] Examples of suitable organic peroxides include dialkyl peroxides, such as diisopropyl peroxide and di-tert-butyl peroxide; ketone peroxides, such as methyl ethyl ketone peroxide, methyl isopropyl ketone peroxide, acetylacetone peroxide, methyl isobutyl ketone peroxide, and cyclohexane peroxide; peroxydicarbonates, such as diisopropyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, disec-butyl peroxydicarbonate, and isopropyl-sec-butyl peroxydicarbonate; peroxyesters, such as tert-butyl peroxy-2-ethylhexanoate and tert-hexyl peroxy-2-ethylhexanoate; diacyl peroxides, such as benzoyl peroxide, acetyl peroxide, and lauroyl peroxide; peroxyketals, such as 2,2-di(tert-butylperoxy)butane, 1,1-di(tert-butylperoxy)cyclohexane, and 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane; and mixtures thereof.

[0048] Examples of suitable organic azo compounds include 2,2'-azobisisobutyronitrile, dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanopentanoic acid), and mixtures thereof.

[0049] According to a preferred embodiment, the catalyst is diisopropyl peroxide (IPP).

[0050] The amount of catalyst in the polymerizable composition according to the invention may be from 1.0% to 5.0% by weight, particularly from 2.5% to 4.5% by weight, and more particularly from 3.0% to 4.0% by weight, based on the total weight of the composition.

[0051] The light-absorbing additive contained in the nanoparticles is a compound capable of absorbing ultraviolet, visible, and / or infrared light, wherein the nanoparticles are dispersed in the composition according to the invention.

[0052] Specifically, the light-absorbing additive may be selected from the group consisting of: colorants, such as dyes or pigments; colorless light-absorbing additives; and mixtures thereof. Examples of suitable dyes, pigments, and colorants are compounds belonging to the families of azo or rhodamine or anthocyanin or polyacetylenes or fluorochrome or pyranonium or porphyrin or phthalocyanine or dinaphthalene or coumarin or acridine or pseudoindole or indole-2-ylene or benzoanthrone or anthraquinone or anthraquinone or benzotriazole or benzophenone or anthraquinone or triazine or oxaloaniline; metal complexes, such as rare earth cavitary compounds or chelates; aluminates, silicates, and aluminosilicates.

[0053] In a particular embodiment, the colorant and colorless light-absorbing additive are blue light absorbers, meaning they absorb visible light in the blue-violet band between 380 nm and 500 nm. This absorption can be specific, where the selective absorber has an absorption peak in the band between 380 nm and 500 nm. This absorption can also be non-specific, but associated with the negative effect of the broadband absorption of the UV absorber.

[0054] When the light-absorbing additive is a blue light absorber, the resulting ophthalmic lens can be characterized by an average transmittance within a specific blue light range, particularly in the range of 420 nm to 450 nm. Preferably, the blue light absorber is selected such that the ophthalmic lens obtained from the polymerizable composition of the present invention has an average transmittance (hereinafter, TB%) of less than 85%, more preferably less than 75%, in the range of 420 nm to 450 nm.

[0055] According to specific embodiments, the blue light absorber included in the composition according to the invention is a metalloporphyrin, particularly a hydrophobic metalloporphyrin.

[0056] According to another embodiment, the blue light absorber included in the composition according to the invention is auramine O; coumarin 343; coumarin 314; proflavin; nitrobenzoxadiazole; fluorescein CH; 9,10-bis(phenylethynyl)anthracene; chlorophyll a; chlorophyll b; 4-(dicyanomethylene)-2-methyl-6-(4-dimethylaminostyryl)-4H-pyran; 2-[4-(dimethylamino)styryl]-1-methylpyridine iodide, 3,3'-diethyloxacarbonyl anthocyanin iodide, lutein, zeaxanthin, β-carotene or lycopene or dinaphthalene; and mixtures thereof.

[0057] According to another embodiment, the blue light absorber included in the composition according to the invention is a porphyrin or a derivative thereof. Some examples of porphyrins include sodium 5,10,15,20-tetra(4-sulfonylphenyl)porphyrin complexes; 5,10,15,20-tetra(N-alkyl-4-pyridyl)porphyrin complexes; 5,10,15,20-tetra(N-alkyl-3-pyridyl)porphyrin metal complexes; and 5,10,15,20-tetra(N-alkyl-2-pyridyl)porphyrin complexes, and mixtures thereof, wherein the alkyl group is selected from methyl, ethyl, butyl, and / or propyl. All of these porphyrins exhibit very good water solubility and are stable up to 300°C. Other examples of porphyrins include diprotonated tetraphenylporphyrin, octaethylporphyrin magnesium, tetra(trimethylphenyl)porphyrin magnesium, tetra(2,6-dichlorophenyl)porphyrin, tetra(o-aminophenyl)porphyrin, tetra(trimethylphenyl)porphyrin, tetra(trimethylphenyl)porphyrin zinc, tetraphenylporphyrin zinc, Mg(II) meso-tetra(4-sulfonylphenyl)porphyrin tetrasodium salt, and manganese(III) chloride 5, 10, 1 5,20-Tetra(4-pyridyl)-21H,23H-porphyrin tetra(methyl chloride), 5,10,15,20-Tetra(4-sulfonylphenyl)-21H,23H-porphyrin manganese(III) chloride, 5,10,15,20-Tetra(4-sulfonylphenyl)-porphyrin-Cu(II), 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphyrin manganese(III) chloride Zinc 5,10,15,20-tetra(4-pyridyl)-21H,23H-porphyrin tetra(methyl chloride), 5,10,15,20-tetra(4-methoxyphenyl)-21H,23H-porphyrin cobalt(II), 5,10,15,20-tetra(4-methoxyphenyl)-21H,23H-porphyrin, 5,10,15,20-tetra(4-methoxyphenyl)-21H,23H-porphyrin iron(III) Chloride, zinc 5,10,15,20-tetra(4-pyridyl)-21H,23H-porphyrin tetra(methyl chloride), 5,10,15,20-tetra(1-methyl-4-pyrido)porphyrin tetra(p-toluenesulfonate), 5,10,15,20-tetra(4-hydroxyphenyl)-21H,23H-porphyrin, 4,4',4″,4'″-(porphyrin-5,10,15,20-tetrayl)tetra(benzoic acid).

[0058] According to another embodiment, the blue light absorber included in the composition according to the invention is a metal complex, wherein the metal may be Cr(III), Ag(II), In(III), Mg(II), Mn(III), Sn(IV), Fe(III), or Zn(II). Metal complexes based on Cr(III), Ag(II), In(III), Mn(III), Sn(IV), Fe(III), or Zn(II) have particular advantages in that they are insensitive to acids and provide more stable complexes because they do not lose the metal at pH < 6.

[0059] In specific embodiments, the colorant and colorless light-absorbing additive are UV absorbers, meaning they absorb UV light in the band below 380 nm. When the light-absorbing additive is a UV absorber, the resulting ophthalmic lens exhibits UV cutoff. "UV cutoff" refers to the highest wavelength with a transmittance of less than 1%, as measured according to the methods described herein. Preferably, the UV absorber is selected such that the ophthalmic lens obtained from the polymerizable composition of the present invention has a UV cutoff of at least 380 nm.

[0060] According to specific embodiments, the UV absorbers included in the compositions according to the invention are benzotriazole, benzophenone, triazine, oxaloyl aniline, and mixtures thereof.

[0061] In specific embodiments, the colorants and colorless light-absorbing additives are near-infrared (NIR) absorbers, meaning they absorb infrared light in the band from about 780 nm to about 1400 nm. In particular, semiquinones or binuclear mixed-valence ruthenium complexes are suitable NIR absorbers.

[0062] The amount of light-absorbing additive in the nanoparticles can be from 0.0001 wt% to 90 wt%, particularly from 0.01 wt% to 50 wt%, and more particularly from 0.1 wt% to 10 wt% based on the weight of the nanoparticles.

[0063] According to the present invention, a light-absorbing additive is encapsulated in nanoparticles dispersed in the composition according to the present invention, that is, the light-absorbing additive is contained within the nanoparticles or grafted onto the nanoparticles.

[0064] Nanoparticles behave like storage containers, storing and protecting light-absorbing additives. The light-absorbing additives can be uniformly dispersed within the nanoparticles or located in the core of the nanoparticles. The light-absorbing additives can also be located on the surface of the nanoparticles or inside the pores of the nanoparticles.

[0065] In practice, the active reactants from the compositions according to the invention, i.e., the free radicals involved in the free radical polymerization, will not be able to diffuse within the internal portions of the nanoparticles. If the light-absorbing additives are located on the surface of the nanoparticles or in the pores of the nanoparticles, the active reactants can reach them, but the likelihood of reaction is reduced and the additives are also protected because the mobility of the grafted or trapped additives is hindered.

[0066] In the context of this invention, the term "nanoparticle" is intended to refer to an individualized particle of any shape having a size, measured in its longest direction, in the range of 1 nm to 10 μm, preferably in the range of 10 nm to 5 μm, as measured by the dynamic light scattering method disclosed herein.

[0067] The nanoparticles of the present invention are polymer-based, i.e., they contain polymers, or mineral-based, i.e., they contain mineral oxides.

[0068] In a preferred embodiment, the polymer or mineral oxide contained in the nanoparticles is a transparent material.

[0069] According to a first embodiment, the nanoparticles dispersed in the composition according to the invention comprise a polymer.

[0070] Polymer-based nanoparticles can come in various types, such as latex nanoparticles, core-shell nanoparticles, nanoparticles grafted with light-absorbing additives, dendritic polymer nanoparticles, and nanoparticles containing polymers with melting points above 120°C. Polymer-based nanoparticles can be further coated with a protective layer.

[0071] Preferably, the polymer-based nanoparticles comprise polymers selected from the group consisting of acrylic polymers, vinyl polymers, allyl polymers, and mixtures thereof. More preferably, the polymer-based nanoparticles comprise copolymers of acrylic polymers, and more preferably methyl methacrylate and ethylene glycol dimethacrylate.

[0072] Polymer-based nanoparticles can be prepared by solvent evaporation, nanoprecipitation, emulsion polymerization, interfacial polymerization, spray drying, and coagulation. Preferably, polymer-based nanoparticles are prepared by emulsion polymerization, such as microemulsion polymerization or fine emulsion polymerization.

[0073] Polymer-based nanoparticles containing light-absorbing additives can be prepared by emulsion polymerization by mixing a solvent, such as water; a light-absorbing additive, monomers, such as acrylic monomers, vinyl monomers, allyl monomers, and mixtures thereof; a mild catalyst, such as an organoazo compound, persulfate, peroxide, or perketal; at least one surfactant, preferably an ionic surfactant, such as sodium dodecyl sulfonate; and optionally a networking agent. The use of ionic surfactants advantageously helps to prevent the coalescence of monomer droplets during polymerization and the aggregation of nanoparticles after polymerization due to ion repulsion. The use of a mild catalyst advantageously prevents the degradation of the light-absorbing additive, which occurs with harsh catalysts such as peroxide. The use of a networking agent advantageously densifies the nanoparticles, thereby preventing leakage of the light-absorbing additive from the nanoparticles during lens polymerization and preventing free radical migration within the nanoparticles.

[0074] In some embodiments, the light-absorbing additive is copolymerizable within polymer-based nanoparticles. "Copolymerizable" means that the light-absorbing additive contains reactive groups, such as unsaturated groups or functional groups, which are capable of forming covalent bonds with the materials used to prepare the polymer-based nanoparticles.

[0075] According to a second embodiment, the nanoparticles dispersed in the composition according to the invention comprise mineral oxides. Preferably, the mineral-based nanoparticles comprise mineral oxides selected from the group consisting of: SiO2, TiO2, ZrO2, Al2O3, and mixtures thereof.

[0076] Mineral-based nanoparticles can be used to... It can be prepared by synthesis or reverse microemulsion method.

[0077] Silica nanoparticles containing light-absorbing additives can be used to... The synthesis involves mixing tetraethyl orthosilicate and a light-absorbing additive in an excess of water containing a low molar mass of an alcohol (such as ethanol) and ammonia. In this process, the light-absorbing additives must be functionalized so that they can form covalent bonds with silica, for example, by silylation with conventional silanes, preferably alkoxysilanes. The synthesis yielded monodisperse SiO2 particles of controllable size.

[0078] Silica or silica-metal oxide nanoparticles containing light-absorbing additives can be prepared via a reverse-phase (water-in-oil) microemulsion method by mixing an oil phase, such as cyclohexane and n-hexanol; water; a surfactant, such as Triton X-100; a light-absorbing additive, one or more mineral oxide precursors, such as tetraethyl orthosilicate, titanium alkoxylate, and aluminum alkoxide; and a pH adjuster (such as sodium hydroxide). In the reverse-phase microemulsion approach, the ratio of light-absorbing additives to water-in-oil can be increased. Synthetic encapsulation of light-absorbing additives involves encapsulating a greater amount of polar light-absorbing additives within a mineral oxide matrix: the encapsulation yield can be very high, thus avoiding the waste of expensive light-absorbing additives. Furthermore, this method advantageously allows for easy control of particle size, especially in the case of reverse microemulsion methods. Additionally, this method enables the addition of TiO2, ZrO2, or Al2O3 to silica nanoparticles.

[0079] pass The mineral-based nanoparticles obtained by synthesis and reverse (water-in-oil) microemulsion methods are highly networked and coated with hydrophobic silica groups, thereby preventing the leakage of light-absorbing additives from the nanoparticles and preventing free radicals from migrating inside the nanoparticles during lens polymerization.

[0080] In a preferred embodiment, as measured according to ISO 489:1999, the refractive index of the nanoparticles is from 1.47 to 1.56, preferably the same as that of the polymerized allyl monomer or oligomer. In fact, when the refractive index of the nanoparticles is close to that of the polymerized allyl monomer or oligomer, the ophthalmic lens exhibits less light scattering and therefore less reduction in light intensity and / or haze.

[0081] The refractive index of polymer-based nanoparticles depends on the type of monomer or monomer mixture used to prepare the nanoparticles. Similarly, the refractive index of allyl nanoparticles is 1.5, and the refractive index of acrylic or vinyl nanoparticles can be increased by copolymerizing acrylic or vinyl monomers with monomers containing aromatic groups.

[0082] The refractive index of mineral-based nanoparticles depends on the type of mineral oxide or mixture of mineral oxides used to prepare the nanoparticles. Similarly, the refractive index of SiO2 nanoparticles is 1.47-1.5, and the refractive index of nanoparticles containing mixtures of SiO2 and TiO2, mixtures of SiO2 and ZrO2, or mixtures of SiO2 and Al2O3 can reach 1.56.

[0083] Advantageously, the nanoparticles exhibit sizes ranging from 1 nm to 10 μm, preferably from 10 nm to 5 μm, as measured by dynamic light scattering. In fact, when the nanoparticle size is less than 10 μm, the ophthalmic lens exhibits less light scattering and therefore less reduction in light intensity. Such nanoparticles can be obtained directly by microemulsion polymerization or by reducing their size through a milling step.

[0084] The amount of nanoparticles in the composition is from 0.01 wt% to 2 wt%, preferably from 0.05 wt% to 1 wt%, based on the weight of the composition.

[0085] Methods for preparing liquid polymerizable compositions and ophthalmic lenses

[0086] The method for preparing the above-mentioned polymerizable liquid composition includes the following steps:

[0087] a) Provide allyl monomers or allyl oligomers;

[0088] b) Provide a light-absorbing additive contained in nanoparticles, the nanoparticles being in the form of a powder of nanoparticles that can be dispersed in the allyl monomer or allyl oligomer, or in the form of a dispersion of the nanoparticles in a liquid that can be dispersed in the allyl monomer or allyl oligomer.

[0089] c) Provide a catalyst for initiating the polymerization of the allyl monomer or allyl oligomer;

[0090] d) Mix the allyl monomer or allyl oligomer, the light-absorbing additive contained in the nanoparticles, and the catalyst.

[0091] The polymerizable liquid composition is then cured to obtain an ophthalmic lens, or deposited as a coating onto an optical substrate and then cured to obtain an ophthalmic lens. Preferably, the curing is thermosetting.

[0092] As used herein, the coating to be deposited on the surface of the substrate is defined as a coating that (i) is placed above the substrate; (ii) is not necessarily in contact with the substrate, that is, one or more intermediate layers may be arranged between the substrate and the layer in question; and (iii) does not necessarily completely cover the substrate.

[0093] Coatings can be deposited or formed using various methods, including wet processing, gas processing, and film transfer.

[0094] According to a preferred embodiment, the composition may be stirred until homogeneous before curing and then degassed and / or filtered.

[0095] According to a preferred embodiment, when nanoparticles are provided in the form of a dispersion in a liquid, wherein the dispersion liquid is a monomer that can be dispersed within an allyl monomer or an allyl oligomer, and in particular, the dispersion liquid is an allyl monomer or an allyl oligomer.

[0096] The polymerizable composition of the present invention described above can be cast into a mold to form a lens and polymerized by heating at a temperature from 40°C to 130°C, preferably from 45°C to 95°C. According to a preferred embodiment, the heating can be sustained for 5 to 24 hours, preferably 7 to 22 hours, and more preferably 15 to 20 hours.

[0097] The mold can then be disassembled, and the lens can be cleaned with water, ethanol, or isopropanol.

[0098] The ophthalmic lens can then be coated with one or more functional coatings selected from the group consisting of: abrasion-resistant coatings, anti-reflective coatings, anti-fouling coatings, antistatic coatings, anti-fog coatings, polarizing coatings, coloring coatings, and photochromic coatings.

[0099] In this context, ophthalmic lenses are defined as lenses designed to fit eyeglass frames to protect the eyes and / or correct vision. These lenses can be uncorrected (also known as plano or afocal lenses) or corrected. Corrected lenses can be monofocal, bifocal, trifocal, or progressive lenses.

[0100] Uses of light-absorbing additives contained in nanoparticles

[0101] This invention also relates to the use of light-absorbing additives contained in nanoparticles to prevent catalytic degradation of the light-absorbing additives when used to initiate the polymerization of allyl monomers or allyl oligomers. The prevention of catalytic degradation of the light-absorbing additives can be assessed by comparing the absorption spectrum of the composition before polymerization with the absorption spectrum of the ophthalmic lens after polymerization. If the absorption spectrum shows the same decrease in transmittance for the maximum absorption wavelength of the light-absorbing additive, it can be assumed that the light-absorbing additives were not degraded by the catalytic agent during polymerization.

[0102] According to a preferred embodiment, a light-absorbing additive contained in the nanoparticles is used to prevent yellowing of the cured allyl-based ophthalmic lens. In practice, the light-absorbing additive is degraded by the catalyst during polymerization, producing degradation products that lead to undesirable lens yellowing. The yellowness index (YI) of the cured allyl-based ophthalmic lens can be measured according to ASTM D-1925.

[0103] Ophthalmic lenses and ophthalmic products

[0104] The ophthalmic lens of the present invention includes a composite substrate, said composite substrate comprising:

[0105] a) A matrix obtained by polymerizing at least one allyl monomer or oligomer in the presence of a catalyst for initiating the polymerization of the allyl monomer or allyl oligomer.

[0106] b) Nanoparticles containing at least one light-absorbing additive, said nanoparticles being dispersed in the matrix.

[0107] In other words, the ophthalmic lens of the present invention comprises a polymer matrix and nanoparticles dispersed therein, wherein the nanoparticles encapsulate light-absorbing additives.

[0108] Therefore, the polymer matrix (also referred to herein as the “matrix”) and the nanoparticles dispersed therein together form a composite substrate, i.e., a composite material with two main surfaces, which correspond to the front and back of the final ophthalmic lens.

[0109] In one embodiment, the ophthalmic lens is essentially composed of a polymer matrix and nanoparticles dispersed therein.

[0110] In another embodiment, the ophthalmic lens includes an optical substrate on which a coating of a polymer matrix and nanoparticles dispersed therein is deposited.

[0111] Due to the intact reticular structure during polymerization, the ophthalmic lens of the present invention exhibits satisfactory mechanical properties.

[0112] The present invention also relates to an ophthalmic lens obtained by curing the polymerizable liquid composition of the present invention.

[0113] The present invention also relates to an ophthalmic lens, the ophthalmic lens comprising:

[0114] a) Optical substrate;

[0115] b) A coating obtained by curing the polymerizable liquid composition of the present invention onto the optical substrate.

[0116] The invention will now be described in more detail by way of the following examples, which are given for purely illustrative purposes and are not intended to limit the scope of the invention in any way.

[0117] Example

[0118] Attached Figure

[0119] Figure 1 It is for light-absorbing additives (OMNISTAB) contained in polymer-based nanoparticles. TM47. A composition with a maximum absorption wavelength of 424 nm. The curves showing the transmittance as a function of wavelength before polymerization (dashed line) and after polymerization (solid line).

[0120] Figure 2 This is a graph showing the transmittance as a function of wavelength for lenses with unencapsulated light-absorbing additives (dashed lines) and light-absorbing additives encapsulated in polymer-based nanoparticles (solid lines).

[0121] Measurement methods

[0122] The following measurements were taken on a lens that was 2 mm thick at its center and had been cleaned with isopropyl alcohol.

[0123] Calculate the average (or average) transmittance (TB%) in the range of 420nm–450nm from the transmittance curve measured according to ISO 8980-3-2003.

[0124] The size of nanoparticles is measured using a standard dynamic light scattering method. This technique measures the time-dependent fluctuations in the intensity of scattered light from a suspension of nanoparticles undergoing random Brownian motion. Analysis of these intensity fluctuations allows for the determination of the diffusion coefficient, which can be expressed as particle size using the Stokes-Einstein relation.

[0125] Using Haze-Guard from BYK-Gardner The haze meter (color difference meter) measures haze values ​​by light transmission measurement according to the method of ASTM D1003-00. All references to "haze" values ​​in this application are in accordance with this standard. First, the instrument is calibrated according to the manufacturer's instructions. Next, the sample is placed on the transmitted beam of this pre-calibrated measuring instrument, and haze values ​​are recorded from three different sample positions and averaged.

[0126] Taking into account a standard light source D65 at an incident angle of 15° and an observer (at an angle of 10°), the colorimetric coefficient of the lens of the present invention is measured (i.e. calculated) between 380 nm and 780 nm according to the International Colorimetric System CIE L*a*b*.

[0127] Material

[0128] In the example described, the following compounds are used:

[0129]

[0130]

[0131] Example 1: Preparation of polymer-based nanoparticles containing light-absorbing additives via microemulsion polymerization

[0132] A monomer blend (5g) was prepared from methyl methacrylate and ethylene glycol dimethacrylate in a 50:50 weight ratio, and OMNISTAB was added. TM 47 (10 mg, available from Deltachem Ltd.) was dissolved in this monomer blend. This blend was added dropwise to 50 ml of an aqueous solution containing SDS (0.5 g) and AIVN (0.05 g) at 80 °C under a nitrogen atmosphere. After the monomer blend addition was complete, the mixture was further mixed at 80 °C for an additional 2 h, then centrifuged, washed with ethanol, and dried. The nanoparticles have a size in the range of 200 nm to 1000 nm and a refractive index of 1.5.

[0133] Dispersing nanoparticles in To prepare masterbatch (masterbatch 1) in monomers (12.5% ​​by weight of nanoparticles).

[0134] Example 2: Preparation of mineral-based nanoparticles containing light-absorbing additives via reverse microemulsion method

[0135] Example 2a: Cyclohexane (7.5 ml), n-hexanol (1.8 ml), Triton X-100 (1.5 g), and OMNISTAB were added. TM A mixture of 47 (40 mg, available from Deltachem Ltd.), TEOS (0.1 ml), and 30% ammonium hydroxide (0.06 ml) was mixed for 24 h. Acetone was then added, and the particles were collected by centrifugation, washed with ethanol, and dried. The nanoparticles had a monodisperse size centered at 100 nm and a refractive index of approximately 1.47 corresponding to precipitated silica.

[0136] Nanoparticles were dispersed in CR-39 (12.5% ​​by weight of nanoparticles in monomer) to prepare masterbatch (masterbatch 2a).

[0137] Example 2b: 7.56 g of Triton X-100, 5.86 g of hexane-1-ol, 23.46 g of cyclohexane, 1.6 ml of deionized water, 0.32 ml of methylene blue solution (CAS: 61-73-4, 1% by weight solution in water) as a light-absorbing additive, 0.4 ml of TEOS, and 0.24 ml of 30% ammonium hydroxide solution in water were mixed and stirred for 24 h at room temperature.

[0138] After 24 hours, 1 volume of acetone (approximately 50 ml) was added to the obtained solution, and the particles were collected by centrifugation, washed with acetone or water, dried overnight at room temperature, and annealed in an oven at 80°C for 3 hours.

[0139] Then, 0.2 g of the obtained dried mineral nanoparticles were redispersed under magnetic stirring in approximately 20 ml of acetone and 1 mm zirconium beads as a grinding agent. The mixture was then filtered to remove the zirconium beads. Then, 99.8 g of [unspecified ingredient] was added. And acetone is vaporized under vacuum to obtain masterbatch (masterbatch 2b).

[0140] Example 2c: At room temperature, 7.56 g of Triton X-100, 30 ml of hexane-1-ol, 7.2 ml of cyclohexane, 1.6 ml of deionized water, 0.32 ml of methylene blue solution (CAS: 61-73-4, 1% by weight solution in water) as a light-absorbing additive, 0.4 ml of TEOS, and 0.24 ml of 30% ammonium hydroxide solution in water were mixed and stirred for 24 h.

[0141] After 24 hours, 1 volume of acetone (approximately 50 ml) was added to the obtained solution, and the particles were collected by centrifugation, washed with acetone or water, and dried overnight at room temperature. The nanoparticles have a monodisperse size of 100 nm and a refractive index of approximately 1.47 corresponding to precipitated silica.

[0142] As in Example 2b, nanoparticles are dispersed in The masterbatch (masterbatch 2c) was prepared by China and Israel.

[0143] Example 2d: A replica of Example 2c (Masterbatch 2d), except that 1.76 ml of deionized water was used instead of 1.6 ml and 7.4 g of Triton X-100 was used instead of 7.54 g. The nanoparticles have a monodisperse size of 80 nm.

[0144] Example 2e: A replica of Example 2c (Masterbatch 2e), except that 2.16 ml of deionized water was used instead of 1.6 ml and 7 g of Triton X-100 was used instead of 7.54 g. The nanoparticles have a monodisperse size of 50 nm.

[0145] Examples 2c to 2e show that the ratio between deionized water and Triton X-100 determines the final size of the nanoparticles: the higher the ratio, the smaller the nanoparticles.

[0146] Example 2f: Reproduced from Example 2c (Masterbatch 2f), except that 1.44 ml of deionized water was used instead of 1.6 ml and 7 g of Triton X-100 was used instead of 7.54 g. Further, 0.16 ml of a 0.01 M solution of 5,10,15,20-tetra(4-sulfonylphenyl)-porphyrin-Cu(II) (TSPP-Cu(II)) was added in deionized water. The nanoparticles had a monodisperse size of 100 nm.

[0147] As summarized in Table A below, other light absorbers have been used with the same preparation procedure.

[0148] Table A

[0149]

[0150]

[0151]

[0152] Example 3: Through A method for preparing mineral-based nanoparticles containing light-absorbing additives.

[0153] Add 384 mL of methanol to a 1000 mL bottle. Then, add 96 mL of NH4OH (30% by weight solution in water) and 6.4 mL of methylene blue (CAS: 61-73-4, 2% by weight solution in deionized water). Stir the mixture at 400 rpm (magnetic stirring) for 10 min. After that, add 3.2 mL of TEOS dropwise and stir at 800 rpm for 2 h.

[0154] After the reaction was complete, the particle size was checked by dynamic light scattering. The average particle size was approximately 200 nm-230 nm (monodisperse).

[0155] The mixture was transferred to a round-bottom flask and evaporated for 1 hour to reduce the methanol volume from 500 ml to 100 ml, then centrifuged at 4000 rpm for 45 min. The supernatant was removed and the nanoparticles were collected as a concentrated dispersion in methanol.

[0156] The mixture was then washed twice using the following procedure: 50 ml of methanol was added under ultrasonic treatment to redisperse the particles. The nanoparticles were collected by centrifugation at 4000 rpm for 30 min.

[0157] The nanoparticles were air-dried overnight at ambient temperature and then ground in an agathe mortar. They were then annealed at 180°C for 2 hours.

[0158] 0.3 g of nanoparticles were mixed with 99.7 g of CR-39 monomer in a 250 ml bottle. The masterbatch was sonicated for 30 min. Centrifuged at 4000 rpm for 30 min to remove agglomerated particles. The supernatant was collected to obtain masterbatch (masterbatch 3).

[0159] Example 4: Preparation of ophthalmic lenses according to the present invention

[0160]

[0161] Monomer blends were prepared by weighing and mixing the components in a beaker at room temperature. First, the... and Mix. Once homogeneous, add the nanoparticles from the masterbatch, then mix the contents of the beaker again until fully dispersed. Finally, add the IPP and stir the mixture thoroughly, then degas and filter.

[0162] The composition was then injected into a 71 mm diameter glass double-sided mold using a syringe, and polymerization was carried out in a regulated electric oven where the temperature was gradually increased from 45°C to 85°C over 15 hours, and then maintained at a constant 85°C for 5 hours. The mold was then removed, and the resulting lens had a thickness of 2 mm at its center.

[0163] like Figure 1 The transmission spectra of the composition containing masterbatch 1 before polymerization and the transmission spectra of the lens after polymerization, as shown, exhibit the same decrease in transmittance at the maximum absorption wavelength (424 nm) of the light-absorbing additive. Similarly, in the ophthalmic lens according to the invention, the dye was not degraded by the IPP catalyst during polymerization. The difference between the two spectra outside the absorption domain of the light-absorbing additive is clearly associated with the chemical transformations that occur during polymerization (catalyst dissociation, reactions of unsaturated groups, etc.).

[0164] like Figure 2 As shown, the resulting ophthalmic lens has an average transmittance of 77% (TB%) in the range of 420 nm to 450 nm. In contrast, the same ophthalmic lens containing unencapsulated dye has an average transmittance of 91% (TB). Similarly, the ophthalmic lens containing encapsulated dye according to the invention exhibits better blue light absorption than the corresponding ophthalmic lens containing unencapsulated dye.

[0165] The effects of methylene blue as a light-absorbing additive on lens haze (light diffusion), particle size, and residual color (as measured by b* according to the CIE Lab model) were evaluated using various nanoparticles. The conditions of Example 2b were replicated, except that the concentration of the methylene blue aqueous solution was varied between 0.4% and 1% in increments of 0.2%, resulting in nanoparticles with different concentrations of methylene blue.

[0166] Increasing the methylene blue concentration in the nanoparticles showed a positive trend for haze reduction, as fewer particles were required to achieve the same coloring effect. Compared to particles obtained with a 0.4% methylene blue solution, particles obtained with a 1% methylene blue solution showed a decrease in average transmittance (TB%) from 0.5 to 0.3 without compromising haze performance.

[0167] Increasing the methylene blue concentration also resulted in an increase in particle size: at 0.4%, the measured particle size was approximately 80 nm, while at 0.6%, the measured particle size was approximately 90 nm, and at both 0.8% and 1%, the measured particle size was 95 nm.

[0168] The measurements also showed that, for similar residual color (measured by b* reduction in the Lab system), the haze produced by nanoparticles washed with deionized water was approximately 20%–40% lower than that produced by nanoparticles washed with acetone.

Claims

1. A polymerizable liquid composition for manufacturing ophthalmic lenses, the composition comprising: a) at least one allyl monomer or allyl oligomer b) At least one catalyst for initiating the polymerization of the allyl monomer or allyl oligomer. c) At least one light-absorbing additive contained within particles, said particles being dispersed in the allyl monomer or allyl oligomer. The particles mentioned above are mineral-based particles prepared via Stöber synthesis. Wherein, as measured according to ISO 489:1999, the refractive index of the particles is from 1.47 to 1.56, and The particles exhibit sizes ranging from 1 nm to 10 µm, as measured by dynamic light scattering.

2. The composition according to claim 1, wherein, The light-absorbing additive is selected from the group consisting of: colorants; colorless light-absorbing additives; and mixtures thereof.

3. The composition according to claim 1 or 2, wherein, The particles contain polymers.

4. The composition according to claim 1 or 2, wherein, The particles contain mineral oxides selected from the group consisting of: SiO2, TiO2, ZrO2, Al2O3, and mixtures thereof.

5. The composition according to claim 1 or 2, wherein, As measured according to ISO 489:1999, the refractive index of the particles is from 1.47 to 1.5, and the particles are SiO2 particles.

6. The composition according to claim 1 or 2, wherein, The particles exhibit sizes ranging from 10 nm to 5 µm, as measured by dynamic light scattering.

7. The composition according to claim 1 or 2, wherein, The amount of light-absorbing additive in the particles ranges from 0.0001 wt% to 90 wt% based on the weight of the particles.

8. The composition according to claim 1 or 2, wherein, The amount of particles in the composition is from 0.01 wt% to 2 wt% based on the weight of the composition.

9. The composition according to claim 1 or 2, wherein, The allyl monomer or oligomer is selected from the group consisting of: diethylene glycol bis(allyl carbonate), ethylene glycol bis(allyl carbonate), oligomers of diethylene glycol bis(allyl carbonate), oligomers of ethylene glycol bis(allyl carbonate), bisphenol A bis(allyl carbonate), diallyl phthalate, diallyl isophthalate, diallyl terephthalate, and mixtures thereof.

10. The composition according to claim 1 or 2, wherein, The catalyst is selected from the group consisting of: peroxides, perketals, and mixtures thereof.

11. The composition according to claim 1 or 2, wherein, The catalyst is dicarbonate peroxide.

12. A method for preparing a polymerizable liquid composition as defined in any one of claims 1-11, the method comprising the steps of: a) Provide allyl monomers or allyl oligomers; b) Provide a light-absorbing additive contained in particles, said particles being in the form of a powder of particles dispersible within the allyl monomer or allyl oligomer, or in the form of a dispersion of said particles in a liquid dispersible within the allyl monomer or allyl oligomer, said particles being mineral-based particles obtained by Stöber synthesis, wherein said particles have a refractive index from 1.47 to 1.56 as measured according to ISO 489: 1999, and said particles exhibit a size from 1 nm to 10 µm as measured according to dynamic light scattering. c) Provide a catalyst for initiating the polymerization of the allyl monomer or allyl oligomer; d) Mix the allyl monomer or allyl oligomer, the light-absorbing additive contained in the particles, and the catalyst.

13. The use of a light-absorbing additive contained in particles for preventing the light-absorbing additive from being used as a catalyst to initiate the polymerization of allyl monomers or allyl oligomers, said particles being dispersed in a polymerizable liquid composition as defined in any one of claims 1-11.

14. An ophthalmic lens obtained by curing a polymerizable liquid composition as defined in any one of claims 1-11.

15. An ophthalmic lens, said ophthalmic lens comprising: a) Optical substrate; b) A coating obtained by curing a polymerizable liquid composition as defined in any one of claims 1-11 onto the optical substrate.

16. An ophthalmic lens comprising a composite substrate, said composite substrate comprising: a) A matrix obtained by polymerizing at least one allyl monomer or oligomer in the presence of a catalyst for initiating the polymerization of the allyl monomer or allyl oligomer. b) Particles containing at least one light-absorbing additive, the particles being dispersed in the matrix, and the particles being mineral-based particles obtained by Stöber synthesis, having a refractive index from 1.47 to 1.56 as measured according to ISO 489: 1999, and exhibiting a size from 1 nm to 10 µm as measured according to dynamic light scattering.

Citation Information

Patent Citations

  • Plastic lenses of good ultraviolet absorbability for spectacles and method for producing them

    EP1085348A2

  • Plastic lenses having good ultraviolet absorbability, and method for the production thereof

    EP1085349A2

  • Microcapsules loaded with active ingredients and a method for their preparation

    EP2263788A2

  • Mesoporous vector containing at least one organic UV filter

    EP2282713A2

  • Eyeglass lens made of allyl diglycol carbonate resin

    US20120188503A1